Development of an improved E. coli bacterial strain for green and sustainable concrete technology. Issue 41 (7th May 2015) - Sarkar, Manas; Alam, Nurul; Chaudhuri, Biswadeep; Chattopadhyay, Brajadulal; Mandal, Saroj
<x xml:space="preserve">Abstract</x> Genetic engineering of an improved bioremediase-like protein in the improvement of eco-friendly sustainable bioconcrete.